Advanced characterisation of multi-recycled warm asphalt pavement (MRWAP) with high content of recycled asphalt pavement. Issue 2 (1st February 2023) - Pouget, S.; Marsac, P.; Pedraza, A.; Sauzéat, C.; Di Benedetto, H.; Gaudefroy, V.; Boulangé, L.; Pévère, A.; Mouillet, V.
Abstract : The main results of the French collaborative project Improvmure, funded by the National Research Agency are presented. A very wide study was performed on bituminous mixtures produced on experimental sites or in laboratory at different scales (semi-industrial process or lab process). Objectives were to evaluate the influence of the recycling rate (0%, 40% and 70%), the number of successive recycling cycles (from 1 to 3 cycles), and the manufacturing process (hot mix or warm mix using additives or foamed bitumen). The impact was studied in laboratory on the emitted fumes during the production process, on the properties used for mix design (compactability, water sensitivity, complex modulus at 15°C/10 Hz, fatigue), on advanced thermomechanical behaviour (linear viscoelasticity, crack behaviour at low temperature, crack propagation) and on surface properties (skid resistance). The paper gathers many valuable results, showing the possibility to recycle bituminous mixtures multiple times, at high rates and with warm manufacturing process.